The use of gold/porous silicon/n-silicon Schottky diodes as non-enzymatic glucose sensors - Arslan, Asli; Yuksel, Sureyya Aydin (ELSEVIER SCIENCE SA, 2026)
In recent years, research on non-enzymatic glucose sensors has intensified. Silicon-based glucose sensors are attracting attention due to their compatibility with MEMS. In this study, a non-enzymatic glucose sensor was fabricated in a Gold (Au)/Pororus Silicon (PS)/ n-type silicon (n-Si) Schottky diode geometry, using a highly doped n-Si substrate with high response compatibility, an insulating PS layer grown by electromagnetic anodization, and Au, known for its catalytic effect on glucose, as the metal electrode layer. The effects of PS and Au layer thicknesses on the glucose sensitivity of the sensors were determined and optimized. Unlike the literature, our sensors, which operate like fuel cells at room temperature without an external power source, showed a high linear relationship between the generated short-circuit current density (Jsc) and open-circuit voltages (Voc) depending on the glucose concentration. This relationship was controlled by changing the Schottky diode barrier height. The electrochemical working mechanism of our electrolyte-interfaced Schottky-based non-enzymatic sensors was supported by Cyclic Voltammetric (CV) and Electrochemical Impedance Spectroscopy (EIS) measurements. It exhibits glucose sensor characteristics with a low detection limit of 58 & micro;M and a sensitivity of 36.6 nA.cm-2 (mg/dl)-1 . This suggests that our PS-based Schottky diode sensors can be used as glucose detection devices in practical biological applications.
Keywords: Porous silicon; Non-enzymatic; Glucose; Schottky diode; ELECTROCHEMICAL BIOSENSORS; ELECTRICAL-PROPERTIES; CARBON NANOTUBES; AU; NANOPARTICLES; ELECTRODES; TRANSPORT; OXIDATION; Engineering; Instruments & Instrumentation